Investigating Instagram’s Influence towards EFL Students’ Learning Motivation - Mulyana, Novita; Puspitaning Adni, Nissa; Bayu Perdana Putra, I Wayan; Adi Wira Laksana, I Made (Humanis, 2025)
Learning motivation is one of the key elements that determine the success of achieving learning outcomes. This study was aimed to investigate the influence of Instagram, a social media, towards English as Foreign Language (EFL) students’ learning motivation when it is used as a learning media. The study utilized mixed method approach to achieve the aforementioned goal. The data collection was conducted by using questionnaire distributed to the second semester students of Bachelor of English Literature Udayana University in the academic year of 2023/2024. The data obtained were further analyzed quantitatively and qualitatively. The quantitative analysis was conducted by utilizing statistical analysis with SPSS. The results were interpreted and analyzed qualitatively by using several theories related to learning motivation. The result of the study shows that the use of Instagram as language learning media contributes positive influence towards the EFL students’ motivation in learning. In other words, the more it is used as a language learning media in the learning process, the higher students’ motivation will be.